Analisis Semiotika Kekerasan dalam Film Drama Korea The Penthouse: War In Life I - Safira, Ratih (Medan Resource Center, 2022)
Analysis of Semiotics of Violence in the Korean Drama Film The Penthouse: War In Life Season 1 (Representation of Violence Scenes in Impressions of 15 Years of Age)